Analysis of the Relationship Between Gratification Seeking, Val-ue Shopping, Idea Shopping, Materialism, and Compulsive Buy-ing on Life Happiness and Self Esteem (Study on Female Con-sumers) - Ayu Sekarsari, Larasati (IQTISHADequity jurnal MANAJEMEN, 2023)
This study examines the relationship between This study examines the relationship between gratification seeking, value shopping, idea shopping, materialism, and compulsive buying on life happiness and self esteem (study on women online consumers). The type of research used is quantitative research through a consumer survey approach. The sampling technique applied is purposive sampling. Data was collected using a survey method through google forms filled out by respondents. The research sample used was 200 female respondents who are E-Commerce users, especially respondents who are in the Surabaya area. Meanwhile, in this study, the tests used in statistical analysis were hypothesis testing with PLS-SEM (Partial Least Square Structural Equation Modeling) and WarpPLS 7.0 software. Based on the management results, (1) Gratification seeking has a significant effect on compulsive buying; (2) Value shopping has no significant effect on compulsive buying : (3) Idea shopping has a significant effect on compulsive buying ; (4) Materialism has a significant effect on compulsive buying ; (5) Compulsive buying has a significant effect on life happiness; and (6) Compulsive buying has a significant effect on self esteem